A New View of a:C-H-coated Ti-6Al-4V Alloy to be Used as Orthopedic Implants: Influence of Surface Free-energy of Interaction on the Biological Responses - Nascimento, João Pedro Lopes; Freitas, Leonardo dos Reis; Lemos, Camila Nunes; Gelamo, Rogério Valentim; Moreto, Jéferson Aparecido (Orbital: The Electronic Journal of Chemistry, 2021)
In a previous published work, the Ti-6Al-4V alloy were functionalized by using plasma enhanced chemical vapour deposition (PECVD) process in order to obtain hydrogenated amorphous carbon (a:C-H) on the biomaterial’s surface. At the time, we noticed the functionalized surface contributed to the advance of using Ti-6Al-4V in biomedical implants applications as well as in the adding of intrinsic properties as demonstrated by electrochemical and biological assays. Here, we present new view of a-C:H-coated Ti-6Al-4V alloy, considering the influence of surface free-energy of interaction and understanding how the surface influences the biological response using pre-osteoblastic cells (MC3T3-61). Our results demonstrate, the Ti-6Al-4V containing a:C-H film has less negative value of surface free-energy when compared to the bare material (-22.156 mJ m-2 vs. -60.046 mJ m-2), suggesting a tendency toward to a less hydrophobic surface which is extremely important to reduce the inflammatory process, common in orthopedic implants. DOI: http://dx.doi.org/10.17807/orbital.v13i3.1622